2019
DOI: 10.1063/1.5092514
|View full text |Cite
|
Sign up to set email alerts
|

Gravitoelectrostatic excitations in an opposite polarity complex plasma

Abstract: The linear and nonlinear properties of gravitoelectrostatic mode, in a plasma system consisting of inertial opposite polarity charged dust grains as well as inertialess nonextensively q-distributed ions and electrons (including the effect of polarization force on the massively charged dust grains), have been investigated. A general dispersion relation has been derived yielding only one eigen wave mode. It is found that the polarization force and the nonextensively distributed ions effects play directly a desta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Using a non-perturbative approach, Abulwafa et al [42] studied DAWs in a four-component dusty plasma with particles obeying non-Maxwellian distribution and showed the coexistence of compressive and rarefactive solitary waves. El-Taibany et al [43] investigated the dynamical behaviors of linear and nonlinear DAWs in the presence of polarization and self-gravitational force. El-Monier and Atteya [18] qualitatively analyzed the bifurcation behavior for DAWs in a multi-component dusty plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Using a non-perturbative approach, Abulwafa et al [42] studied DAWs in a four-component dusty plasma with particles obeying non-Maxwellian distribution and showed the coexistence of compressive and rarefactive solitary waves. El-Taibany et al [43] investigated the dynamical behaviors of linear and nonlinear DAWs in the presence of polarization and self-gravitational force. El-Monier and Atteya [18] qualitatively analyzed the bifurcation behavior for DAWs in a multi-component dusty plasma.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the presence of a polarization force leads to a decrease in the Mach number regime where solitary structures can exist. El-Taibany et al [41] investigated the linear and nonlinear features of gravitoelectrostatic opposite polarity dusty plasma in the framework of the Sagdeev potential approach, taking into account the effect of polarization force on the negatively charged dust grains. They found that the real wave frequency is reduced by the presence of polarization force.…”
Section: Introductionmentioning
confidence: 99%
“…But there is direct evidence for the co-existence of both positively and negatively charged dust particles in different regions of space plasmas such as, the Earth's mesosphere [17], cometary tails [18], Jupiter's magnetospheres [19] and laboratory devices [20]. Recently, El-Taibany et al [21] have studied the effects of polarization force on the electrostatic solitary waves. But they have ignored the effects of polarization force on the positive dust.…”
Section: Introductionmentioning
confidence: 99%